The aerobic performance of trained and untrained handcyclists with spinal cord injury - Lovell, D.; Shields, D.; Beck, B.; Cuneo, R.; McLellan, C. (European Journal of Applied Physiology, 2012)
The purpose of this study was to compare the cardiorespiratory response and mechanical efficiency (ME) of highly trained spinal cord injured (SCI) handcyclists with untrained SCI men. Ten trained handcyclists (>2 years training) and ten untrained but physically active SCI men completed an incremental exercise test to exhaustion and a sub-maximal test (50 and 80 W) on an electromagnetically braked arm ergometer. The trained participants completed a questionnaire on their training and race performance over the past year, including average training volume (in kilometers), number of training sessions per week and best 20-km time trial. The trained SCI men had higher VO2 peak, peak power (p < 0.001) and peak heart rate (p = 0.021) compared to the untrained SCI men. The trained men had higher (p < 0.001) ME at 50 W (14.1 ± 2.0%) and 80 W (17.2 ± 2.6) compared to the untrained men (50 W; 12.5 ± 1.8 and 80 W; 15.7 ± 2.1). Peak power (r = -0.87, p = 0.001), VO2 peak (r = -0.67, p = 0.033) and ME (r = -0.58, p = 0.041) were negatively correlated with the participants best 20-km time trial. Multiple linear regression indicated peak power (p < 0.001) and VO2 peak (p = 0.021) were the best predictors (87%) of 20-km time trial performance. Highly trained SCI handcyclists have a greater aerobic capacity and ME compared to untrained SCI, and are able to reach their maximum age-predicted heart rate during an incremental exercise test. The best predictor of 20 km race performance in highly trained SCI handcyclists is peak power attained during an incremental exercise test.